Energy Storage Application into a Double DC Electric Railway. (October 2018) - Alnuman, Hammad; Gladwin, Daniel T.
Abstract: Electric trains use regenerative braking to improve the energy efficiency of DC electric railways. The regenerative braking power can cause overvoltage in the feeding line if it is higher than the power demand of the other trains at that instant. Braking resistors are activated to burn the excess energy to protect the network from overvoltage that originates from braking. This excess energy can be exploited by using an energy storage system (ESS). However, a stationary ESS may increase energy loss in the transmission line if its location is not optimal. This paper helps prove that the negative effect of a stationary ESS can be eliminated by optimal siting and voltage control.